Website design and implementation Foundation insan madani center - Annisa Arsy Tiara; Khairil Khairil; Devi Sartika (Penerbit Jurnal Indonesia, 2023)
The design and implementation of this website aims to create information media for the public to obtain information about Insan Madani Center Foundation. This research uses research and development (R&D) method which is used to produce a website product and test the effectiveness of the website. The steps used are data collection, product design then validating the design, website testing and website implementation. The implementation of this website itself used framework code igniter for web application network to build dynamic PHP applications and for the database using MySQL. Based on the trial results of this research, website application for Insan Madani Center Foundation can be built as an information media and can be accessed online with the domain merdekainsanic.org.